Increased Thromboxane Metabolites Excretion in Liver Cirrhosis - Davì, Giovanni; Ferro, Domenico; Basili, Stefania; Iuliano, Luigi; Camastra, Caterina; Giammarresi, Carlo; Santarone, Stella; Rocca, Bianca; Landolfi, Raffaele; Ciabattoni, Giovanni; Cordova, Corrado; Violi, Francesco (Thrombosis and Haemostasis, 1998)
An augmented systemic production of thromboxane (TX) A2, as assessed by urinary excretion of the thromboxane metabolites, has been described in severe liver cirrhosis. However, the significance of this finding remains unclear since in liver cirrhosis a number of phenomena i.e. altered hepatic TXA2 metabolism, increased intrasplenic platelet destruction, may affect TXA2 entry into systemic circulation as well as its metabolism. In order to further clarify this, we measured both major enzymatic metabolites of TXB2 in the urine of 44 patients affected by liver cirrhosis, subdivided in three classes on the basis of Child-Pugh criteria. Urinary 11-dehydro-TXB2 and 2,3-dinor-TXB2 were assayed with previously validated RIA techniques.The urinary excretion rate of 11-dehydro-TXB2 was significantly (p = 0.0001) increased in the cirrhotic patients (673.5 pg/mg cr, median) in comparison with the controls (275 pg/mg cr, median) but no significant difference could be demonstrated among the excretion rates of the three patient subgroups. The excretion rate of 2,3 dinor-TXB2 was also significantly (p = 0.0001) increased in the patients (824 pg/mg cr, median) in comparison with controls (175 pg/mg cr, median), with a significant (p <0.05) increase from class A (381 pg/mg cr) to class C (1337 pg/mg cr). The sum of the two enzymatic metabolites was significantly (p = 0.0001) increased in the cirrhotic patients in comparison to controls, with a progressive increase from class A (1003 pg/mg cr, median) to class C (2240 pg/mg cr, median). The urinary excretion of 2,3 dinor-TXB2 was significantly (p = 0.008) related to plasma prothrombin fragment 1+2 (F1+2).This study provides further evidence of increased thromboxane biosynthesis in liver cirrhosis. Moreover, we demonstrate intraliver shift of thromboxane metabolic disposition, due to progressive liver decompensation, because only the fraction undergoing β-oxidation to 2,3-dinor-TXB2 was progressively increased with the degree of liver failure. We, also, find a significant correlation between urinary excretion of 2,3-dinor-TXB2 and plasma F1+2, suggesting that clotting activation could partly account for in vivo platelet activation.